Terapia farmacológica en insuficiencia cardiaca fracción de eyección reducida: ¿cómo, cuánto, a quién? - Cañete P., Iván; de la Carrera V., Agustín; Gil L., Antonia; Orchard B., Ian; Llancaqueo V., Marcelo; Bustamante M., Sergio (Revista Hospital Clínico Universidad de Chile, 2024)
Heart failure (HF) is a clinical syndrome characterized by a combination of symptoms and signs caused by structural and/or functional cardiac abnormalities, confirmed by elevated levels of natriuretic peptides and/or objective evidence of pulmonary or systemic congestion (1-2).Guidelines have been proposed to guide treatment based on the left ventricular ejection fraction (EF), dividing it into three categories: HF with preserved EF (EF > 50%), HF with mildly reduced EF (EF 40-49%), and HF with reduced EF (EF < 40%). Currently, certain drugs have demonstrated a reduction in mortality and morbidity. When combined, these drugs provide an even greater synergistic benefit. In 2021, the European Society of Cardiology (ESC) published an editorial regarding the best therapy for HFrEF. These drugs include Inhibitors of the Renin-Angiotensin- Aldosterone System (IERAA), Beta-Blockers (BB), Mineralocorticoid Receptor Antagonists (MRA), and Sodium-Glucose Cotransporter Inhibitors (iSGLT2), also known as the “four horsemen.” The initiation of these four combined drugs represents the optimal therapy for HFrEF. However, individual patient profiles should be considered to provide personalized, optimal therapy, taking into account potential side effects. This work aims to summarize the key points as outlined by the ESC regarding optimal therapy for HFrEF and how to choose it.